2021
DOI: 10.1177/17448069211047863
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of adenylyl cyclase subtype 1 reduces inflammatory pain in chicken of gouty arthritis

Abstract: Lack of uricase leads to the high incidence of gout in humans and poultry, which is different from rodents. Therefore, chicken is considered to be one of the ideal animal models for the study of gout. Gout-related pain caused by the accumulation of urate in joints is one type of inflammatory pain, which causes damage to joint function. Our previous studies have demonstrated the crucial role of calcium-stimulated adenylyl cyclase subtype 1 (AC1) in inflammatory pain in rodents; however, there is no study in pou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…These results of hNB001 are in consistent with previous animals' studies using NB001 which is designed for research tool in the lab. [12][13][14]17,28,31 With dose escalation, the exposure of hNB001 increased proportionally, suggesting linear PK. Before the start of this study, the HED of hNB001 20 mg/kg in rats was estimated to be approximately 200 mg for a man with 60 kg body weight.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These results of hNB001 are in consistent with previous animals' studies using NB001 which is designed for research tool in the lab. [12][13][14]17,28,31 With dose escalation, the exposure of hNB001 increased proportionally, suggesting linear PK. Before the start of this study, the HED of hNB001 20 mg/kg in rats was estimated to be approximately 200 mg for a man with 60 kg body weight.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have also demonstrated the analgesic effect of NB001 on animal models of gouty arthritis, migraine, and Parkinson's disease-related pain. [17][18][19][20] The analgesic effect of NB001 is believed to be produced by inhibiting several central synaptic mechanisms that are critical for chronic pain and related emotional changes. 21 They include the following: cortical postsynaptic long-term potentiation (post-LTP) and presynaptic long-term potentiation (pre-LTP) in the ACC and IC, 5 activation of various immediate early genes, 22,23 upregulation of NMDA receptors 24 after injury, new protein synthesis of AC1 after injury, 15 spinal LTP and serotonin-induced facilitation.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that adenylyl cyclase subtype 1 (AC1) is involved in the regulation of gouty pain in chickens. A selective AC1 inhibitor NB001 produces an analgesic effect (not anti-inflammatory effect) on gouty pain and may be used for the future treatment of gouty pain in both humans and poultry [ 57 ].…”
Section: Physiopathology Of Viral Infection Induced Goutmentioning
confidence: 99%
“…Research on avian coronavirus found that a significant increase in xanthine oxidase (XOD) activity in serum and a significant increase in serum uric acid levels were related to nephropathogenic IBV infection with increased uric acid synthesis and inhibited peroxisome functions [ 67 ]. It has been reported that the NMDAR-AC1-TRPA1 pathway may participate in the regulation of gouty pain in chickens [ 57 ]. For gout in goslings, young goslings are high-risk groups of visceral gout.…”
Section: Physiopathology Of Viral Infection Induced Goutmentioning
confidence: 99%
“…The inhibition of AC1 could also help attenuate pain sensitization beyond the primary zone of injury through changes in functional plasticity that occurs in contralateral sensory nerves following the induction of inflammation (Kelly et al, 2007) that may not follow the same time course as the ipsilateral side. AC1 inhibition most likely does not impact the progression of inflammation directly, as other studies have shown that NB001, does not impact CFA-Frontiers in Pharmacology frontiersin.org induced knee joint structural destruction nor mono-sodium urateinduced edema of the ankle joint (Tian et al, 2015;Liu et al, 2021). Alternatively, those results may be explained by the smaller overall level of the Adcy1 knockdown in our studies when compared to global AC1 knockout mice (Wei et al, 2002).…”
Section: Discussionmentioning
confidence: 53%